Genomic variability and alternative splicing generate multiple PML/RAR alpha transcripts that encode aberrant PML proteins and PML/RAR alpha isoforms in acute promyelocytic leukaemia. - Pandolfi, P P (1992)
The acute promyelocytic leukaemia (APL) 15;17 translocation generates a PML/RAR alpha chimeric gene which is transcribed as a fusion PML/RAR alpha mRNA. Molecular studies on a large series of APLs revealed great heterogeneity of the PML/RAR alpha transcripts due to: (i) variable breaking of chromosome 15 within three PML breakpoint cluster regions (bcr1, bcr2 and bcr3), (ii) alternative splicings of the PML portion and (iii) alternative usage of two RAR alpha polyadenylation sites. Nucleotide sequence analysis predicted two types of proteins: multiple PML/RAR alpha and aberrant PML. The PML/RAR alpha proteins varied among bcr1, 2 and 3 APL cases and within single cases. The fusion proteins contained variable portions of the PML N terminus joined to the B-F RAR alpha domains; the only PML region retained was the putative DNA binding domain. The aberrant PML proteins lacked the C terminus, which had been replaced by from two to ten amino acid residues from the RAR alpha sequence. Multiple PML/RAR alpha isoforms and aberrant PML proteins were found to coexist in all APLs. These findings indicate that two potential oncogenic proteins are generated by the t(15;17) and suggest that the PML activation pathway is altered in APLs.